2012
DOI: 10.3139/217.2525
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Fiber Breakage during Compounding in a Buss Kneader

Abstract: International audienceThis paper is devoted to the study of fiber breakage during compounding with a polyamide matrix in a Buss kneader. Results showed a drastic decrease of glass fiber length during compounding, typically from 3500 to 350 mu m. Fiber breakage depended on processing conditions: it increased with screw speed, but the effect of feed rate was less clear. Fiber breakage increased also with the severity of the screw profile. Characterizations of fiber length evolution along the screw profile have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…The materials are the same as in the previous studies (Inceoglu et al, 2011;Ville et al, 2012). The matrix is a Polyamide-12 (PA12), kindly supplied by Arkema (France).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The materials are the same as in the previous studies (Inceoglu et al, 2011;Ville et al, 2012). The matrix is a Polyamide-12 (PA12), kindly supplied by Arkema (France).…”
Section: Methodsmentioning
confidence: 99%
“…In this so-called modified model, either the number of turns or the specific energy is taken into account, even though specific energy seems to be more appropriate to calculate fiber breakage. The results predicted from the model highlight the effect of mixing conditions (screw speed and feed rate) and of the screw profile on fiber length distribution (Inceoglu et al, 2011;Ville et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…When a ber reinforced composite was prepared by a different processing machine, the bers suffered because of the varied breakage caused by those machines. Ville et al 17 studied ber breakage during compounding with a polyamide matrix in a Buss kneader. They found that the composite mixed with a Buss kneader had shorter average ber length than that one mixed with a twin screw extruder.…”
Section: Introductionmentioning
confidence: 99%